Library Anxiety: Stories, Theories and Possible Solutions. Issue 4 (2nd October 2018) - Shelmerdine, Anna J.
Abstract : This issue, in collaboration with the State Library of New South Wales, we are pleased to feature the 2018 winner of the Jean Arnot Memorial Fellowship. The Fellowship is awarded to a female librarian or student of librarianship for an outstanding paper of no more than 5000 words on any aspect of librarianship. Papers focusing on innovative solutions to contemporary library issues and services are encouraged. The fellowship is named in honour of the late Jean Fleming Arnot, MBE, FLAA, a former staff member of the State Library of New South Wales. Miss Arnot retired as head cataloguer in 1968 after a distinguished career of over 47 years. Miss Arnot was active in women's organisations and a pioneer in the campaign for equal pay for women. The Jean Arnot Memorial Fellowship is funded by a generous donation from the National Council of Women of New South Wales and the Australian Federation of Business and Professional Women's Associations to commemorate Miss Arnot and her achievements. An award of 1000 is presented to the winner at the annual Jean Arnot Memorial Luncheon at NSW Parliament House. The Fellowship has been running for more than 20 years and is judged by a panel chaired by the Mitchell Librarian. Some of the previous award winners are listed on the following web sitehttp://www.sl.nsw.gov.au/fellowships/jean-arnot-memorial-fellowship